Access to credit in Argentina - Bebczuk, Ricardo N. (CEPAL SantiagoCL, 2007)
Examines the access to credit by financially constrained SMEs in Argentina over the last decade, focuses on the role played by public banks, state credit policies, and non-traditional lending contracts such as leasing, factoring, microcredit and others. Proposes a number of practical guidelines to strengthen the effectiveness, transparency and accountability of governmental credit policies.